REDUCING STRESS IN SCHOOL CHILDREN THROUGH THE USE OF SOME DANCE TECHNICAL ELEMENTS AS A FORM OF THERAPY - E.F. GROSU; H.I. VARI; V.T. GROSU; A.RUSU; C. POPOVICI (Editura Universitatii Transilvania din Brasov, 2020)
Dance therapy, after numerous researches, has proven to be a very beneficial exercise. We are considering reducing stress by applying an intervention plan based on a succession of specific dance steps, artistic program, made by entirely for this purpose. Our results show that the initial measurement, after the intervention program, students were able to greatly reduce mental tensions by further discharged their muscle tension. Certain indicators of stress can be improved by practicing a moment of sport dance with art therapy effect.